Transcriptomic analysis of phosphate utilization OsRHL1 transgenic lines in rice - LIU, DONGBIN (2018)
Understanding and optimising the response of plants to soil nutrient conditions is of central importance in enhancing food security. Root hairs are known to play important role for the uptake of nutrients and water from the rhizosphere and therefore worthy of study. OsRHL1 is a novel basic helix-loop-helix transcription factor that regulates root hair development in rice. Previous studies from Professor Ping Wu’s group (Ding et al., 2008)’s group show that OsRHL1 may regulate genes involved in both root hair elongation and epidermal cell patterning in rice. These studies have shown the important role of OsRHL1 in enhancing root hair growth and phosphate uptake in hydroponic growing systems. Further study for OsRHL1 transgenic line growing in soil was therefore suggested. The overarching aim of this project is to understand the function of the OsRHL1 gene through transcriptomic approaches. Firstly, the gene expression pattern of OsRHL1 was studied using transcriptomic data. The microarray data from OsRHL1 over-expression transgenic rice line and its wild type control was then used to map out the components of the gene network that regulates root hair development in rice. Results obtained from Gene Expression Omibus (GEO) and GeneVestigator using available transcriptomic data suggest that the expression of OsRHL1 is mainly in the root and also present in floral pollen which was not reported previously (e.g. Ding et al. 2008). The gene was found to be involved in the drought and salt tolerance pathways, as well as hormone cytokinins pathway. Furthermore, results obtained from the microarray data analysis of OsRHL1 over-expression and wild type KAS control indicate that OsRHL1 interacts with a series of genes involved in cell wall preproduction, material transporting, and genes that regulate root hair tip growth. It also suggests that a key gene involved in phosphate uptake OsSPX2 is among the components of gene networks contributing to long root hairs in OsRHL1 over-expression transgenic line. The hydroponic growth experiments undertaken in this work suggests that root hair length does play a role in phosphate uptake. OsRHL1 over-expression transgenic plant with long root hair was found to be associated with increased phosphate uptake and resulted in longer shoots and better root growth in low phosphate conditions. The total shoot phosphate content in the OsRHL1 over-expression transgenic line is also significantly higher than the wild type control and its short-hair mutant rhl1. This trend was not detected in hydroponic solution with high levels of phosphate. This result suggests that the length of root hair does play an important role in root phosphate uptake in plant growth medium when the phosphate is less available. This role is less important when there is sufficient phosphate in the medium.